(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The purpose of the study was to identify the possibilities of using modern digital technologies in physical education of students in the educational environment of the university. At the first stage of the research, a theoretical analysis of publications devoted to various aspects of the use of digital technologies in physical education of university students was carried out. The research was based on the scientific journals "Theory and Practice of Physical Culture" and "Physical Culture: upbringing, education, training" for 2020-2021. At the second stage, a sociological survey of 1st year students of Surgut State University was conducted to identify the attitude of students to the use of mobile applications and electronic educational resources in the process of physical education.